Maarak Bungo Lamang at Maulid Nabi (the Prophet Muhammad's Birthday) Ceremony in Nagari Luak Kapau, South Solok Regency (Study: Form, Procession and Meaning) - Hidayat, Febri; Elida, Elida (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This study explained Maarak Bungo Lamang in Nagari (district) Luak Kapau, South Solok Regency. Maarak Bungo Lamang is one of Nagari Luak Kapau traditions to welcome the birthday of Prophet Muhammad SAW or Maulid Nabi among the people of Nagari Luak Kapau, which still exists today with a study of form, procession, and meaning. This study described the problem of form Bungo Lamang, the procession Maarak Bungo Lamang, the meaning of Maarak Bungo Lamang in the Prophet's Birthday ceremony in Nagari Luak Kapau. This research was conducted with a qualitative approach, with a descriptive method. The data were collected using observation techniques, literature study, interviews, and documentation. The research instrument was the researcher himself as the key instrument. The research location was in Nagari Luak Kapau, South Solok Regency. The informants of this research were the leader of the district (wali Nagari), heads of jorong, artists, religious teachers, traditional leaders, and local communities. The data analysis technique used was the data analysis model of Miles and Humberman in Sugiyono. The results of this study indicated that Maarak Bungo Lamang is a traditional ceremony that has existed for a long time. Starting from Bungo Lamang, which used to be just a cooked lamang decorated with newsprint, has been made to vary with the times. Bungo Lamang consists of cooked lamang decorated with oil paper, cardboard, wood talampuang, shell, etc. The Maarak Bungo Lamang procession is carried out after the prayer midday until before the Asr prayer by surrounding Luak Kapau Nagari from the Nagari border to the field. The community still maintains the meaning of Maarak Bungo Lamang in Luak Kapau Nagari as a form of gratitude for the birth of the Prophet Muhammad or what is commonly called the Maulid Nabi.